Clinical Approaches to Orthodontic Appliance Selection in Children with Dentognathic Deformities Complicated by Anatomical and Functional Tongue Disorders - Melnyk, Альона; Kaniura, Олександр; Filonenko, Валерій (Actual Dentistry, 2026)
Anatomical and functional disorders of the tongue, whether syndromic or non-syndromic, can complicate the symptom complex of dentognathic apparatus (DGA) deformities in the sagittal, vertical, and transverse dimensions, or serve as one of the causes of their development. Removable and fixed preventive, therapeutic, and retention orthodontic appliances are used in Ukraine and worldwide to treat dentognathic deformities (DGD). Aim. To systematize the experience of using orthodontic appliances in the treatment of children with DGD complicated by anatomical and functional disorders of the tongue. Materials and methods. This publication reflects the author’s subjective perspective on the choice of orthodontic appliances, based on clinical experience and objective methods of analyzing the effectiveness of orthodontic treatment in children with DGD. The study included patients with non-syndromic anatomical and functional disorders of the tongue (n = 88; 87.1%) and patients with syndromic pathology of the tongue, confirmed or unconfirmed by molecular genetic testing (n = 13; 12.9%). Results and discussion. In children with DGD complicated by anatomical and functional tongue disorders, the use of orthodontic appliances with an expanded plastic maxillary base is limited. Whenever possible, such appliances should be replaced with frame elements (lingual protractor arches, hand-shaped activators, spring-loaded snake-shaped or figure-eight pushers, etc.), supplemented with functional components designed to stimulate tongue tone. Conclusions. In treating children with sagittal, vertical, or transverse dentognathic deformities complicated by anatomical and functional tongue disorders, myofunctional therapy plays a leading role. Primary restoration of tongue function helps prevent the development of persistent forms of DGD. When selecting orthodontic appliance designs, preference should be given to frame elements that promote normalization of the tongue’s physiological position.